Social Factors of Violence among Secondary School Students: A Fieldwork Study of the Schools of Erbil - المدرس اىٍصاغد آشٔ وىٖ ٌطٍد (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This study aims to identify the social factors embodied by family formation, economic level of the family, social status of the family, educational level of the family, school environment leading to the different sorts of school (physical, verbal and/or psychological) violence. The above aim is achieved through a fieldwork testing of the research variables, based on theoretical and methodological framework. To fulfill the above aim and collect sufficient data for the study, a questionnaire was designed, 80 copies of which have been distributed on the participants, who were headmasters, headmaster assistants and teachers. For the verification of the research hypotheses, the researcher has used a set of appropriate statistical methods, which were developed to address the problems of the study. The study has arrived at a number of conclusions. The most important ones are the existence of a relationship between the social factors and the school violence; and the existence of a discrepancy from the point of view of the sample of the study in terms of the impact of social factors on student motivation towards school violence. The study has also proposed a set of suggestions: the necessity of holding training courses for headmasters, their assistants and the teachers on how to deal with violence among students and to acquire the ways of controlling eliminating the phenomenon of school violence. Among the suggestions are the following: raising the economic status and educational level of families and providing suitable places within schools for the students’ refreshment, and holding athletic, and cultural activities. Conducting further studies on the subject has also been suggested.